Face Recognition Locker - Shembekar, Ashlesha; Zade, Khushbu; Malghade, Aniket; Tumaskar, Pradyumna; Dewani, Sagar (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Face recognition has been one of the most interesting and important research fields in the past two decades. The reasons come from the need of automatic recognitions and surveillance systems, the interest in human visual system on face recognition, and the design of human-computer interface, etc. The use of face recognition can be used in locker for the security purpose. By using face recognition locker, the locker can be opened by recognizing the face of user. Therefore, for face recognition the concept of image processing can be implemented.
Keywords: face recognition; openCV; raspberry pi-4; security